Morphological and biological characteristic of bitterling fish (Rhodeus sp.) from river Karashik (Experimental biology, 2016)
Alien species – species which has been introduced in water bodies beyond their natural distribution intentionally or accidentally. In order to increase the diversity of fish fauna in Kazakhstan waters basins were regularly conducted acclimatization of alien species. However, check-in types in a new environment lead to change ecosystems: make an impact on the local fish fauna, replace niche imprint. Aborigine species are competitors in the stern-based local inhabitants. Therefore, the study of alien species becomes more pressing issue. One of the planned acclimatization of valueable species were brought a new alien species – bitterling (Rhodeus sp.). It refers to the weedy alien species. It shoul be noted, that the biology of bitterling from Syr Darya Basin has poorly studied. This study examines the current status and morphological and biological characteristics of bitterling (Rhodeus sp.) from river Karashik. Were analyzed the results of morphological and biological features.
Keywords: fish fauna; acclimatization; bitterling fish; alien species; morphology; biology.